EFFECT OF COVID 19 ON POULTRY INDUSTRY - M Salman Khan; M Taimoor Shahzad Khan; Abrar Ayub; Arslan Aslam; Abdul Basit; Muhammad Hamza (Green Publisher, 2022)
In the wake of the avian flu pandemic, the poultry sector was severely disrupted. Restaurant closures had a negative influence on the demand for chicken, which resulted in supply modifications for broiler growers. Estimating farmer losses is complicated because of the industry's vertical integration. There is no clear correlation between a price decline in broiler chickens and a price drop in other commodities because the farmers do not own the birds. Methods to better understand COVID-19's farm-level implications are discussed in this article